Factors Influencing Recombinant Protein Secretion Efficiency in Gram-Positive Bacteria: Signal Peptide and Beyond - Peng, Chong; Shi, Chaoshuo; Cao, Xue; Li, Yu; Liu, Fufeng; Lu, Fuping (Frontiers in Bioengineering and Biotechnology, 2019)
Signal peptides are short peptides directing newly synthesized proteins towards the secretory pathway. These N-terminal signal sequences are ubiquitous to all prokaryotes and eukaryotes. Signal peptides play a significant role in recombinant protein production. Previous studies have demonstrated that the secretion amount of a given target protein varies significantly depending on the signal peptide that is fused to the protein. Signal peptide selection and signal peptide modification are the two main methods for the secretion optimization of a recombinant protein. However, the highly efficient signal peptide for a target protein with a specific bacterial expression host is not predictable so far. In this review, we collect several signal peptides that have previously performed well for recombinant protein secretion in gram-positive bacteria. We also discuss several factors influencing recombinant protein secretion efficiency in gram-positive bacteria. Signal peptides with a higher charge/length ratio in n-region, more conserved residues at the -3 and -1positions in c-region and a much higher proportion of coils are more likely to perform well in the secretion of recombinant proteins. These summaries can be utilized to the selection and directed modification of signal peptides for a given recombinant protein.